Understanding the workweek of foreign born workers in the United States - Fernando Antonio Lozano (Institute for the Study of Labor (IZA), 2009)
I analyze the length of the workweek of foreign-born workers in the U.S. I concentrate on workers supplying long hours of work - 50 or more weekly hours and document that immigrants are less likely than natives to work long hours. Surprisingly, these differences are greatest among highly educated and salary paid workers, and persists even after conditioning for demographic characteristics. I explain these differences with two within occupation characteristics. First, relative to natives, immigrants are less likely to supply long work weeks if they work in occupations where the immigrant-native earnings differential is big. Second, immigrants are also less likely to supply long work weeks when they work in occupations with a wide dispersion of earnings. This second result is important, because the occupation dispersion of earnings has been used to characterize changes of the worker's earnings over the worker life cycle (Bell and Freeman, 2001; Kuhn and Lozano, 2008), and a good measure of the incentives to supply long hours of work.
urn:nbn:de:101:1-20090825566
Keywords: J22; J61; 330; Immigrants; hours of work; Migranten; Arbeitszeit; Arbeitsangebot; Lohnstruktur; USA